Functional Approach in Teaching and Learning Plane Trigonometry - Magat, Marita Salvo (International Journal of Scientific Research and Management (IJSRM), 2018)
Functional approach is both content and learner based approach of teaching Plane Trigonometry.  As a content-based approach, it is anchored more on the concepts of circles and their applications rather than the concepts of angles.  As a learner-based approach, it is based on Sticht theory of functional context learning which stresses the importance of making learning relevant to the experiences of the learners and their work context.This study investigated the effect of functional approach in the mathematics performance of college students.  It likewise looked into its effectiveness in developing conceptual understanding, computation and problem solving skills and the factors associated with the development of these skills.  It employed the quasi-experimental method specifically the non-equivalent pretest-posttest control group design.  Findings revealed that the functional approach is more effective in raising the performance of students to the standard level in conceptual understanding, computation and problem solving skills than the traditional approach. It was also found out that factors such as previous ratings in mathematics, scholastic aptitude, attitude towards mathematics and gender are associated with development of the three mathematics skills.  Income of the family is not associated with mathematics skills development.  Functional approach in teaching Plane Trigonometry is recommended since it is anchored on the concepts of circles and circular functions which offers sound background materials for the study of higher mathematics and a high potential for the development of conceptual, computational and problem solving skills because it make use of students’ daily work context. Keywords: Functional approach; teaching-learning strategy; Plane Trigonometry